Examining the Impact of Code-Switching on Students' Paragraph Writing in EFL Classrooms - Medhin Mekuria, Markos; Mohammed, Nuru (Universitas Muhammadiyah Barru, 2025)
The use of learners' first language (L1) within target language instruction remains a contentious issue in language education. This study investigated the impact of code-switching on students' paragraph writing performance in target Language (L2) classroom. Employing an experimental research design, data were gathered through pre-tests, post-tests, and semi-structured interviews. The participants consisted of second-year university students enrolled in a Sophomore English course, which focuses on foundational writing skills. Based on pre-test results, 68 students majoring in Dawro Doonaa (Dawro language) were systematically divided into two groups: a control group (n = 33), where English was used exclusively as the medium of instruction, and an experimental group (n = 35), where code-switching to the first language was permitted. Upon completion of the instructional intervention, post-tests were administered, and two instructors were interviewed to provide additional insights into student performance. Statistical analysis conducted using SPSS version 26 revealed no statistically significant difference in overall paragraph writing performance between the two groups (p = 0.46). Nevertheless, the experimental group demonstrated marked improvement in specific dimensions of writing, notably explicitness and idea development. These findings underscore the potential pedagogical value of judicious L1 use, suggesting that EFL instructors and policymakers should critically assess its role rather than entirely exclude it from classroom practice.